Development of technology and manufacturing of an import-substituting complex of machines for cultivating crops - R. S. Rakhimov; I. R. Rakhimov; D. A. Yalaletdinov; E. O. Fetisov; Ya. Yu. Khamitov; R. M. Yumaguzhin; A. R. Rakhimzhanov; S. V. Anokhin (Аграрная наука Евро-Северо-Востока, 2020)
A variety of topography, climate, vegetation and soil of the Southern Urals indicates the need to choose the technology and complex of machines for cultivating crops in accordance with the conditions of the zone and economy. Analysis of existing crop cultivation technologies showed the need for their improvement. To ensure the possibility of changing the methods of soil cultivation and sowing depending on soil and climatic conditions, the cultivated crop and the place of culture in crop rotation, a universal technology is proposed, which provides for the need to create conditions for growth and development of plants based on accumulation and economical use of moisture with application of working bodies and a complex of tillage and sowing machines appropriate to the conditions of the zone. The types of working bodies for basic, additional and presowing tillage and sowing of agricultural crops by various methods are substantiated. The degree of universalization of combined machines for farms with different areas of arable land is established. For small farms with arable land up to 1200 ha, one universal machine with replaceable working bodies or modules is needed to perform primary, secondary and pre-sowing tillage and sowing. For medium-sized farms with arable land up to 10 thousand hectares, separate universal machines with replaceable working bodies are needed for primary tillage, with replaceable modules for additional tillage, and tillage sowing machines with replaceable modules with different types of working bodies are necessary for pre-sowing tillage and sowing. For large farms with arable land area of over 10 thousand hectares it is necessary to use combined single-purpose machines. Based on the previously conducted studies, using the obtained mathematical models and agrotechnical requirements for developing new machines, calculations were carried out and the design parameters of machine complex for tractors of 1.4...5 traction class were substantiated. They were produced by LLC Chelyabinsk Compressor Plant and Varnaagromash LLC with various degrees of universalization The complex of machines for cultivating agricultural crops developed and produced at these plants for various types of farms makes it possible to fulfil all the elements of the proposed technology adopted in the zone in accordance with the agrotechnical requirements as well as soil and climatic conditions of the zone.